Unraveling The Tangled Threads in The Handling of Corruption Crime & Its Impact on The Effectiveness of The Criminal Justice System in Indonesia - Alfies Sihombing; Yeni Nuraeni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Handling corruption in Indonesia is a crucial issue that affects the integrity and effectiveness of law enforcement. Based on Law No. 31 of 1999 amended by Law No. 20 of 2001, corruption includes various acts that harm state finances, such as abuse of authority and bribery. Data from Transparency International shows that corruption remains a serious problem with Indonesia's Corruption Perception Index in 2023 scoring 34 out of 100. This research aims to provide academic insights and practical policy recommendations to improve the effectiveness of law enforcement and corruption eradication in Indonesia. The main focus of this research is on institutional reform, improving supervision, and strengthening accountability to strengthen the integrity of the criminal justice system and increase public trust in law enforcement institutions. This research uses a normative juridical methodological approach by utilizing various analytical techniques, including comparative, conceptual, and statutory approaches. This research shows that structural and procedural weaknesses in handling corruption in Indonesia, such as unclear legal definitions and weak institutional coordination, hinder the effectiveness of corruption eradication. Legal reforms, structural improvements, and strengthened oversight are needed to improve the justice system, build public trust, and support equitable social and economic development.